Investigating Pre-service Chemistry Teachers’ Problem Solving Strategies: Towards Developing a Framework in Teaching Stoichiometry - Allen A. Espinosa; Rebecca C. Nueva España; Arlyne C. Marasigan (Journal of Education in Science, Environment and Health)
The present study investigated pre-service chemistry teachers’ problem solving strategies and alternative conceptions in solving stoichiometric problems and later on formulate a teaching framework based from the result of the study. The pre-service chemistry teachers were given four stoichiometric problems with increasing complexity and they need to write the process that they undertake to solve the problem. The study found out that the most prominent strategy among pre-service chemistry teachers is the mole method, which is algorithmic by nature. Very few of them used the proportionality method and none made use of the logical method. Alternative conception noted among the pre-service chemistry teachers is that some of them rely on Avogadro’s number in converting between moles with a given mass. The results indicate that these pre-service chemistry teachers has the tendency to teach stoichiometry using the mole method only and that they might carry on the alternative conception about Avogadro’s number as they start their teaching career. It is therefore suggested that the teaching of stoichiometry to pre-service chemistry teachers should not be confined to demonstration as they will imitate such technique when they are already a full pledged chemistry teacher. They should be involved in the process of thinking of ways to solve the stoichiometric problem in such a way that it will help them become independent thinkers and be responsible for their own learning by developing metacognitive and critical thinking strategies.